Korelasi Jenis Kelamin Ikan dengan Jumlah Endoparasit pada Ikan Layur (Trichiurus lepturus) yang diperdagangkan di Pasar Ikan Kedonganan, Bali - Dewi, Ni Luh Putu Ayu Puspita; Julyantoro, Pande Gde Sasmita; Wijayanti, Ni Putu Putri; Suryaningtyas, Endang Wulandari (Bumi Lestari; Vol 23 No 2 (2023), 2023)
Swordfish ( Trichiurus lepturus ) with the local name Layur is one of the demersal fish commodities that has high economic value because it is an export commodity with high omega 3 content.. The high demand for layur fish must be supported by good fish quality and quality. The quality control is needed related to fish diseases, one of which is fish parasites. Endoparasite infection in marine fish can be zoonotic and dangerous if consumed by humans. This research was conducted to determine the intensity, prevalence, abundance and correlation of fish sex with the number of endoparasites. The research sample was obtained from the Kedonganan Fish Market, Bali which was held from September 2022 to November 2022. The sampling method was carried out by purposive sampling by paying attention to the secondary sexual characteristics of the swordfish. The total sample of fish examined was 36 fish consisting of 18 male fish and 18 female fish. Endoparasites of the genus Acanthobothrium were parasites with the highest intensity and abundance values, namely 46.05 ind./fish and 28.14 ind./fish, while the highest prevalence value was obtained from the Genus Lecithochirium of 86.11%. The correlation between fish sex and the number of endoparasites was analyzed using the Mann – Whitney test with an Asymp value. Sig 0.506 and Z value -0.665. These results showed an insignificant relationship (p > 0.05) between the sex of the fish and the number of endoparasites in the whitefish that were sampled in this study. Keywords: Endoparasites; Gender; Number of Parasites; Trichiurus lepturus